Uji Efek Stimulan Sistem Saraf Pusat Dari Ekstrak Etanol Biji Pala (Myristica fragrans H.) Pada Mencit Putih Jantan - Delladari Mayefis; Shinta Sari Dewi; Nurlia Oktaviyanti; Arie Vonikartika (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Research on the effects of central nervous system stimulants from nutmeg (Myristica Fragrans H.) ethanol extract on male white mice has been carried out using the methods of: sleep onset test, hanging test, swimming test, and evacuation test. In this study, the test animals were divided into five groups in which each group consisted of three animals for three experiments, the first group was given a 0.5% NaC CMC suspention, the next three groups were given extracts of nutmeg seed ethanol (Myristica Fragrans H. ) with three variations of doses, namely 150, 300, and 600 mg / Kg BW, the next group as a comparison was given a caffeine solution of 13 mg / kg BW. Each preparation was given orally and then carried out a observation of several test methods. The results showed that the ethanol extract of nutmeg (Pala H.) can provide a good stimulant effect at a dose of 300 mg / kg BW (p <0.05) which was clearly seen in the swimming test and the hanging test method.